Surface properties of nanocrystalline TiO2 coatings in relation to the in vitro plasma protein adsorption. (30th July 2015) - Lorenzetti, M; Bernardini, G; Luxbacher, T; Santucci, A; Kobe, S; Novak, S
Abstract: This study reports on the selective adsorption of whole plasma proteins on hydrothermally (HT) grown TiO2 -anatase coatings and its dependence on the three main surface properties: surface charge, wettability and roughness. The influence of the photo-activation of TiO2 by UV irradiation was also evaluated. Even though the protein adhesion onto Ti-based substrates was only moderate, better adsorption of any protein (at pH = 7.4) occurred for the most negatively charged and hydrophobic substrate (Ti non-treated) and for the most nanorough and hydrophilic surface (HT Ti3), indicating that the mutual action of the surface characteristics is responsible for the attraction and adhesion of the proteins. The HT coatings showed a higher adsorption of certain proteins (albumin 'passivation' layer, apolipoproteins, vitamin D-binding protein, ceruloplasmin, α -2-HS-glycoprotein) and higher ratios of albumin to fibrinogen and albumin to immunoglobulin γ -chains. The UV pre-irradiation affected the surface properties and strongly reduced the adsorption of the proteins. These results provide in-depth knowledge about the characterization of nanocrystalline TiO2 coatings for body implants and provide a basis for future studies on the hemocompatibility and biocompatibility of such surfaces.